Aid Coordination and Delivery : Yemen Policy Note 5 - World Bank Group (World Bank, Washington, DC, 2017)
This policy note outlines options for aid coordination and delivery in Yemen. It draws on a vast amount of experiences and lessons learned from post-conflict recovery and peace building processes both in Yemen and elsewhere over the past decade.Its central message is that timely international support and targeted financial aid will be critical to the implementation of a new peace agreement in Yemen, but delivery ofthis support will have to be carefully designed, sequenced, and coordinated in order to overcome divisions and assist Yemen in addressing the challenges driving the cyclical nature of conflict in the country.This note highlights the importance of focusing efforts in the immediate termon sequencing and coordinating while the conflict is ongoing, and negotiations move forward to support immediate recovery programming once negotiations achieve a positive outcome.This note argues that the peace dividend, that is recovery and development, and humanitarian assistance need to be effective immediately to build peace and overcome the causes of conflict. At the same time such arrangements should strengthen national systems and capacities that are needed toeliminate poverty, promote development objectives, and help to build peace.These challenges are compounded by the fact that expectations will be extremely high during the immediate aftermath of the latest round of conflict,absorptive capacity will remain limited for years to come, and the government capacity to deliver will be hindered by its lack of access and legitimacy in certain parts of the country even following a peace agreement.